Efektivitas Unplugged Coding untuk Meningkatkan Berpikir Komputasi dalam Pembelajaran Matematika Siswa Sekolah Dasar - Khujaimah; Wiryanto; Mariana, Neni (Department of Mathematics Education, Faculty of Tarbiyah and Teacher Training, UIN Sunan Ampel Surabaya, 2025)
This study aims to (1) Measure the improvement in students' computational thinking skills before (pretest) and after (posttest) the implementation of Unplugged Coding-based mathematics learning; (2) To compare the improvement in computational thinking skills between the experimental and control groups; and (3) To analyze the aspects of computational thinking (decomposition, pattern recognition, abstraction and algorithms, and evaluation) that showed the most significant development. The study used a quasi-experimental design with a sample of 31 fourth-grade students from SD Negeri Dukuh Sari 1 Sidoarjo, and 31 students from SD Negeri Waru 1 Sidoarjo. Data was collected using a test technique that assessed computational thinking ability. The data were analyzed using ANOVA to test for differences in final abilities between groups, while controlling for initial abilities (pretest scores). The prerequisite tests were normality and homogeneity tests. This study concluded that: (1) There was a very significant increase in computational thinking skills in the experimental group with a gain score of 45.5 points, (2) Unplugged Coding was significantly more effective than conventional learning (F = 662.18; p < 0.001; η² = 0.917), and (3) The algorithm and decomposition aspects showed the most dominant development.